Systematic review and meta-analysis of determinants associated with HPV vaccination uptake in Europe. (30th September 2020) - Costantino, C; Tabacchi, G; Sannasardo, C E; Scarpitta, F; Vella, C; Vitale, F; Casuccio, A; Restivo, V
Abstract: Background: Human papillomavirus (HPV) vaccines are the most important strategy to prevent HPV-related cancers and benign lesions. However, low immunization levels observed in several countries requires a deeper analysis of determinants associated with HPV vaccination uptake. Aim of the research is to identify the main determinants associated with HPV vaccination uptake among European adolescents, through a systematic literature review and meta-analysis. Methods: The research was conducted on electronic databases including PubMed/MEDLINE and SCOPUS, identifying 1147 studies. Original articles published between 2000 and 2018 were retrieved, with restriction criteria applied to the European region and to the English language. Qualitative and quantitative studies describing the positive and negative determinants underlying vaccination uptake were analyzed. Adjusted and Crude Odds Ratios and their Confidence Intervals were extracted and included in the meta-analysis. Results: After screening and eligibility processes, 28 articles were included in the meta-analysis. HPV vaccination uptake is significantly associated with correct information given by health-care workers, educational interventions organized at school about HPV and a gynecologist visits. Receiving information from parents and/or friends and a lack of information about HPV are significantly associated with lower vaccination adherence. Moreover, low socio-economic status and religious conviction represent additional barriers to HPV vaccination adherence. Conclusions: One of the main future challenge for public health authorities will be the increase of HPV vaccination coverage rates. To reach this objective should be necessary to provide an unambiguous communication to general population and to promote educational interventions in the school setting. by all HCWs that play a key role in HPV vaccination recommendation (public health physicians, gynecologists, general practitioners, pediatricians). Key messages: Health-care professionals play a key role in HPV vaccine recommendation, contributing to vaccination acceptance. Tailored and standardized educational intervention in school settings could improve knowledge and beliefs on HPV vaccines, improving adolescents and parents confidence towards vaccination.